Modeling Water Flux in Forward Osmosis: Implications for Improved Membrane Design - Al Mazrooei, Muna (2013)
A Master of Science thesis in Chemical Engineering by Muna Al Mazrooei entitled, "Modeling Water Flux in Forward Osmosis: Implications for Improved Membrane Design," submitted in May 2013. Thesis advisor is Dr. Raafat Alnaizy and co-advisor is Dr. Ahmed Aidan. Available are both soft and hard copies of the thesis.